Leverage, Dividend Policy, and Profitability Effects on IDX30 Stock Price Volatility During 2019–2023 - Siti Maysaroh; Anita Handayani (Jurnal Ilmiah Manajemen Kesatuan, 2025)
The capital market is an increasingly popular investment alternative among the public. One of the factors that can affect stock price volatility is a company's financial statements, which serve as the primary basis for analyzing its performance. This study aims to determine the effect of leverage, dividend policy, and profitability on stock price volatility. This study employs a quantitative method with data analysis conducted using multiple linear regression analysis. The variables used in this study include leverage, dividend policy, and profitability as independent variables, while stock price volatility serves as the dependent variable. Leverage is measured by the Debt-to-Equity Ratio, dividend policy is measured by the Dividend Payout Ratio, and profitability is measured by Return on Assets. The study focuses on companies listed in the IDX30 index on the Indonesia Stock Exchange for the period 2019–2023, using a sample of 63 companies. The results indicate that leverage and dividend policy do not have a significant effect on stock price volatility, while profitability has a negative effect on stock price volatility. Furthermore, leverage, dividend policy, and profitability, when analyzed simultaneously, do not have a significant effect on stock price volatility in the IDX30 index during the 2019–2023 period.